Comparative analysis of microbial communities between water and sediment in Laoshan Bay marine ranching with varied aquaculture activities. (December 2021) - Fang, Guangjie; Yu, Haolin; Sheng, Huaxiang; Tang, Yanli; Liang, Zhenlin
Abstract: We profiled and compared the bacterial and protist community compositions and dynamics in the Laoshan Bay marine ranching involving varied aquaculture activities. The dominant species, differential species and community compositions among the five aquaculture areas, two habitats and two periods were significantly different. The relationships between microbial communities and environmental factors were analyzed. We found that microbial communities in the water were more sensitive to the environmental changes than sediment, and the responses of bacterial and protist communities to the disturbances were varied. To meet the challenges of higher aquaculture density, the proportion of the positive correlations among co-occurrence networks in the water increased markedly from July to November; while the positive proportion in the sediment was stable. Potential ecological interactions and keystone taxa between bacteria and protists were studied. These results advanced our understanding of how mariculture stressors affect microbial communities in marine ranching. Highlights: Microbial communities in the marine ranching with varied aquaculture activities were studied. Artificial reefs and raft cultures influenced the sediment and water microbial communities. The responses of bacteria and protists to varied mariculture were different. The protist community in the marine ranching was more stable against the disturbances.